Управління збутовою діяльністю в системі інноваційного розвитку аграрних підприємств - Пивоваров, Сергій Васильович; Ніценко, Віталій; Зозуля, Ілля Анатолійович (Національний технічний університет "Харківський політехнічний інститут", 2024)
Стаття присвячена дослідженню процесу управління збутовою діяльністю в системі інноваційного розвитку аграрних підприємств. Визначено, що управління збутовою діяльністю є стратегічно важливим елементом функціонування аграрних підприємств. Воно безпосередньо впливає на прибутковість, конкурентоспроможність і стійкість підприємства в умовах динамічного ринкового середовища. Встановлено, що інноваційний розвиток аграрних підприємств передбачає впровадження сучасних цифрових технологій, автоматизацію процесів, розвиток електронної комерції, використання CRM-систем та аналітичних інструментів для прогнозування попиту і оптимізації збуту. Доведено, що ефективна система управління збутовою діяльністю охоплює планування, організацію, контроль та аналіз збутових процесів. Вона повинна інтегрувати маркетингові інструменти, логістику та управління відносинами з клієнтами.

The article is devoted to the study of the process of managing sales activities in the innovative development system of agricultural enterprises. It is determined that sales management is a strategically important element of agricultural enterprises' functioning. It directly affects the profitability, competitiveness, and sustainability of the enterprise in a dynamic market environment. It is established that the innovative development of agricultural enterprises involves implementing modern digital technologies, process automation, the development of e-commerce, the use of CRM systems, and analytical tools for forecasting demand and optimizing sales. It has been proven that an effective sales management system encompasses planning, organization, control, and analysis of sales processes. It should also integrate marketing tools, logistics, and customer relationship management. It is reasonable that adaptation to modern market trends requires diversification of sales channels: the use of traditional intermediary schemes, direct sales, e-commerce and partnerships with marketplaces. Thus, sales management in agricultural enterprises' innovative development systems is a key factor in their success. It promotes adaptation to market changes, ensures increased efficiency of sales processes, and allows enterprises to take stable positions in domestic and foreign markets.
Sales management in the system of innovative development of agricultural enterprises
Keywords: аграрні підприємства; збутова діяльність; інноваційний розвиток; конкурентоспроможність; логістика; маркетинг; agricultural enterprises; innovative development; competitiveness; logistics; marketing; management